Pengaruh Efek Antipiretik Pemberian Kombinasi Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Danekstrak Etanol Daun Lengkeng (Dimocarpus Longan L.)Pada Tikus Putih Betina - Oktifanny Oktifanny; Mevy trisna (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2022)
A study has been carried out on the effect of the antipyretic effect of giving a combination of ethanol extract of starfruit leaves (Averrhoa bilimbi L.) and ethanol extract of longan leaves (Dimocarpus longan L.) in female white rats induced by intraperitoneal 5% peptone 5 ml/head with the aim of knowing combination effect and determining the effective dose as an antipyretic.Temperature measurements were carried out for 2 hours with 30 minute intervals. Measurement results data were analyzed statistically using the ANOVA method with the one way Anova method. The data obtained are normally distributed and have a homogeneous variant. With Fcount ≤ Ftable where there is no significant difference between Paracetamol and the test solution. It can be concluded that the ethanol extract of starfruit leaves (Averrhoa bilimbi L.) and the ethanol extract of longan leaves (Dimocarpus longan L.) are efficacious as antipyretics at doses (25+20) mg/200 g BW, doses (50+40) mg/200 g BW and dose (100+80) mg/200 g BW and the percentage of effect strength against paracetamol was obtained respectively 61.1%, 77.3%, 86.4%.